Integrating response surface methodology and finite element analysis for model updating and damage assessment of multi-arch gallery masonry bridges - Shimpi, Vinay; Sivasubramanian, Madappa V R; Singh, S B (Sadhana (Bangalore), 2024)
This article presents a sophisticated approach to updating the finite element model of two historical arch masonry bridges located in the challenging terrain of Kalka Shimla mountain railway, using vibration testing results. To estimate the dynamic characteristics of the bridges, ambient vibration testing was carried out. Next, initial finite element models of the bridges were developed based on geometrical survey data. Sensitivity analysis was used to determine which parameters needed to be modified for the bridges. The response surface method and global optimization techniques were employed to identify the optimal values of structural parameters that would result in a satisfactory agreement between the numerical and measured natural frequencies of the heritage bridges. Ultimately, the methodology provided a surrogate mathematical model to represent the relationship between structural parameters and dynamic response, and could predict the damage status of the historical bridges.